2014
DOI: 10.1002/jor.22713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic treatments on the depth-dependent viscoelastic shear properties of articular cartilage

Abstract: Osteoarthritis (OA) is a disease that involves the erosion and structural weakening of articular cartilage. OA is characterized by the degradation of collagen and proteoglycans in the extracellular matrix (ECM), particularly at the articular surface by proteinases including matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs).1 Degradation of collagen and proteoglycans is known to alter shear mechanical properties of cartilage, but study of this phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 30 publications
6
49
0
Order By: Relevance
“…However, as it still permits detection of significant differences with various MRI parameters, it provides a model of changes possibly comparable to relatively early changes in OA and is thus relevant despite the modest changes observed. This highlights the importance of spatial analysis of cartilage properties and the importance of spatial reference methods . Another factor potentially affecting the observed differences is that the samples in the different groups were adjacent tissue, and may slightly differ due to natural biological variation.…”
Section: Discussionmentioning
confidence: 98%
“…However, as it still permits detection of significant differences with various MRI parameters, it provides a model of changes possibly comparable to relatively early changes in OA and is thus relevant despite the modest changes observed. This highlights the importance of spatial analysis of cartilage properties and the importance of spatial reference methods . Another factor potentially affecting the observed differences is that the samples in the different groups were adjacent tissue, and may slightly differ due to natural biological variation.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, our group demonstrated that enzymatic pre‐treatment of cartilage explants with trypsin for 2 min were able to promote proteoglycan depletion extending from the center of the cartilage annuli in about 200 μm thick, dramatically influencing cellular migration and promoting better cartilage horizontal integration in an in vitro model . Trypsin enzymatic pre‐treatment of the cartilage results in proteoglycan depletion in a time‐dependent manner, not affecting collagen network and results in increased cell volume and total proteoglycan deposition on partial‐thickness cartilage defects in rabbits . Furthermore, chondrocyte proliferation was shown to increase post‐intra‐articular injection of trypsin in rabbits …”
Section: Discussionmentioning
confidence: 99%
“…In a related sets of experiments, Griffin et al . 31 examined the effects of collagenase and trypsin treatments on microscale changes in the shear modulus of cartilage plugs. Confocal reflectance micrographs revealed increasing collagen degradation caused by collagenase, but not by trypsin, but both treatments caused GAG loss, decreases in the dynamic (viscoelastic) shear modulus, and increased energy dissipation confined to the upper 400 μm of SZ tissue, as assessed by confocal strain mapping.…”
Section: Tissue Mechanicsmentioning
confidence: 99%